Analysis of Information Technology Governance in the Transportation Agency using the Cobit 4.1 Framework - Edo Septiawan; Silfia Andini; Sri Rahmawati (Universitas Putra Indonesia YPTK Padang, 2024)
Information technology plays a role in supporting the goals of companies and government agencies by providing a fast, easy and accurate information and communication platform, increasing the effectiveness and efficiency of the planning process, and supporting innovation in companies and government agencies to develop. The existence of Information Technology has experienced development and the relationship between its operational roles in running an organization, where it is not only as a support for operations. Research was conducted at the Transportation Agency which concluded that the old system used was ineffective because the process carried out took time and space, making employee performance less efficient. After searching for data at the Transportation Agency by collecting data, it can be concluded that the information system used is still not optimal. Therefore, a system design was carried out. The results of the analysis were applied to a cobit system application program. After the research was conducted, the results of the calculation of the maturity model level obtained an average index of 3.16 ( Level 3). This means that the system. The new information system designed is expected to improve the quality of information and performance in the future